Aplikasi Kompos Limbah Kulit Kopi Terhadap Bibit Kopi Arabika Var. Komasti (Coffea arabika L.) - Dewi, Dian Murdianti; Hartatie, Dian; Supriyadi, Supriyadi; Harlianingtyas, Irma; Cahyaningrum, Descha Giatri (Agropross : National Conference Proceedings of Agriculture, 2022)
This activity was carried out to determine the optimal dose of application of coffee husk waste compost on Arabica var. Komasti (Coffea arabica L.) coffee seedlings. It was carried out at the Jember State Polytechnic Collection Garden from November 2018 to April 2019. The research method used was a non-factorial randomized block design with 5 treatments and 5 replications. Treatment A0 = 0 gr/seed (without coffee husk compost), A1 = 150 gr/seedling compost, A2 = 300 gr/seedling, A3 = 450 gr/seedling, A4 = 600 gr/seedling. From the results of data analysis carried out, the application of coffee husk waste compost on the growth of Arabica coffee seedlings had a significant effect on the parameters of seedling height at 146 HSP, wet weight of seeds, and dry weight of seeds. The result of the research activity was that A4 treatment gave the best results with a dose of 600 g of compost fertilizer/seedling. Furthermore, the parameters of the number of leaves and seedling diameter showed no significant (non-significant) results.